The Quest for Critical Thinking Framework in ELT - Hamzah Puadi Ilyas (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
Even though some authors argue that critical thinking (CT) is almost impossible to be taught to students in non-Western countries since Western and non-Western countries have different cultural background, several studies on CT conducted in Asia, Africa and predominantly Muslim countries have showed that it can be taught to non-Western students. CT has actually been fashionable in non-Western countries, and several non-Western countries have nowadays included it in their educational agenda. In spite of CT’s gaining popularity in non-Western countries, there is very little information as regards what kind of CT which is adopted in those non-Western countries’ education and what CT framework which can work in their teaching-learning processes, especially in the field of ELT. This article attempts to propose a critical thinking framework that can be used in ELT as well as other school subjects. The framework is the result of critically analyzing, examining and synthesizing 20 critical thinking taxonomies, strategies, programs and tests.